Antibiotic use in infancy and the risk of asthma in Mexican American children. (9th August 2015) - Eldeirawi, Kamal M.; Kunzweiler, Colin; Atek, Abdulkarim; Persky, Victoria W.
Abstract: Objective : This study examined the associations of antibiotic use in infancy with lifetime doctor-diagnosed asthma and current wheeze among Mexican American children. Methods : In a population-based, cross-sectional investigation, parents of 2023 children 4–18 years of age completed a questionnaire/interview addressing respiratory conditions, antibiotic use, and covariates. Results : In adjusted analyses, among children without history of ear infections in infancy, children who used antibiotics ≥3 times and 1–2 times were more likely to report doctor-diagnosed asthma compared with their peers who did not use antibiotics in infancy [adjusted odds ratio (aOR) = 5.14, 95% confidence interval (CI): 2.88–9.17, and aOR = 2.15, 95% CI: 1.26–3.69, respectively, p trend < 0.0001]. The respective aORs for current wheeze were 3.67 (95% CI: 1.95–6.89) and 1.63 (95% CI: 0.91–2.95). Antibiotic use in infancy was not associated with asthma or current wheeze in children who had ear infections in infancy. In additional analyses, antibiotic use in infancy was associated with asthma in children without parental history of asthma or allergies (aOR = 2.73, 95% CI: 1.70–4.39) but not in those with parental history of asthma or allergies. Among Mexico-born participants born in rural areas, antibiotic use in infancy was associated with a seven-fold increase in risk of asthma (aOR = 7.21, 95% CI: 1.46–35.65), while the association was non-significant in Mexico-born children born in urban areas in Mexico. Conclusions : Antibiotic use in infancy may increase the risk of asthma and wheezing, but these associations were limited to subgroups of children.